2020
DOI: 10.1186/s13662-020-03003-2
|View full text |Cite
|
Sign up to set email alerts
|

General conformable estimators with finite-time stability

Abstract: In this paper, some estimators are proposed for nonlinear dynamical systems with the general conformable derivative. In order to analyze the stability of these estimators, some Lyapunov-like theorems are presented, taking into account finite-time stability. Thus, to prove these theorems, a stability function is defined based on the general conformable operator, which implies exponential stability. The performance of the estimators is assessed by means of numerical simulations. Furthermore, a comparison is made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…More recently in (Khalil et al, 2014), the first conformable calculus was introduced that is an alternative to conformal calculus, but with local operators, without memory. These conformable operators can improve the performance of conformal operators for example (see Meléndez-Vázquez et al, 2021;Reyes-Luis et al, 2021;Meléndez-Vázquez et al, 2020), since these operators can introduce a function that conformal operators cannot, regardless of the non-integer order of these derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…More recently in (Khalil et al, 2014), the first conformable calculus was introduced that is an alternative to conformal calculus, but with local operators, without memory. These conformable operators can improve the performance of conformal operators for example (see Meléndez-Vázquez et al, 2021;Reyes-Luis et al, 2021;Meléndez-Vázquez et al, 2020), since these operators can introduce a function that conformal operators cannot, regardless of the non-integer order of these derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a lot of research and description done on it, and we recommend the following references to the readers [17–22]. After that, a new extension for the conformable fractional derivative is described; see previous studies [23–25]. Indeed, the authors demonstrated the solution's uniqueness and its continuous dependency on the source function and initial‐boundary conditions in Li et al [23].…”
Section: Introductionmentioning
confidence: 99%